2022
DOI: 10.3390/app12042059
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Problems Analysis and Assessment of the Ecological Security Level of the Transboundary Ural-Caspian Basin of the Republic of Kazakhstan

Abstract: Both the insufficiency of water resources and the contamination of even transboundary water bodies are serious problems. Water quality analyses of the transboundary (between Russia and Kazakhstan) Ural River and the Kazakh sector of the Caspian Sea, and their assessment are the main research questions of this study. It is shown that the Ural River is heavily contaminated by polychlorinated biphenyls, heavy metals, oil contaminants, and pesticides, arising from industrial enterprises and agricultural objects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Oil production near the Caspian Sea covers extensive areas of the coastal zone, especially on the south coast [ 56 ], which would explain our results. However, the discharge of petroleum products into rivers could be another important source of pollution, since every year 75,000 tons of these products are discharged into the rivers that flow into the Caspian Sea [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oil production near the Caspian Sea covers extensive areas of the coastal zone, especially on the south coast [ 56 ], which would explain our results. However, the discharge of petroleum products into rivers could be another important source of pollution, since every year 75,000 tons of these products are discharged into the rivers that flow into the Caspian Sea [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported specific challenges such as land cultivation and transboundary reservoir pollution, highlighting the multifaceted nature of water security issues in Kazakhstan (Sembayeva et al, 2023;Amirgaliev et al, 2022). Additionally, the prioritization of water resources and security by regional countries post-independence reflects the broader significance of this issue (Duzdaban, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Каспий балықтарының бұлшықеттерінде мұнай көмірсутектерінің, хлорорганикалық пестицидтердің және ауыр металдардың жоғары мөлшері жинақталуы анықталған (Amirgaliev et al, 2022).…”
Section: кіріспеunclassified